2018
DOI: 10.1039/c7cc09036f
|View full text |Cite
|
Sign up to set email alerts
|

Selective hydrogenation of nitroarenes using an electrogenerated polyoxometalate redox mediator

Abstract: The 2-electron reduced form of the polyoxometalate silicotungstic acid (H[SiWO]) is shown to be an effective and selective hydrogenation agent for a range of nitroarenes without the need for any co-catalyst. The ease of generation of the active species and its recyclability suggest that a new approach to this important class of chemical conversions is possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…The Na 0.44 MnO 2 -based electrode has previously been employed in sodium ion batteries and so displays the required sodium ion intercalation/deintercalation properties; its redox Figure 17. Organic transformations mediated by reduced silicotungstic acid prepared by decoupled water electrolysis: a) Reductions of nitroarenes as reported by MacDonald et al [87] b) Hydrogenation of phenylacetylene and acetophenone as reported by Wu et al [85] waves are also almost exactly midway between the onset potentials of hydrogen and chlorine evolution.…”
Section: -mentioning
confidence: 87%
See 2 more Smart Citations
“…The Na 0.44 MnO 2 -based electrode has previously been employed in sodium ion batteries and so displays the required sodium ion intercalation/deintercalation properties; its redox Figure 17. Organic transformations mediated by reduced silicotungstic acid prepared by decoupled water electrolysis: a) Reductions of nitroarenes as reported by MacDonald et al [87] b) Hydrogenation of phenylacetylene and acetophenone as reported by Wu et al [85] waves are also almost exactly midway between the onset potentials of hydrogen and chlorine evolution.…”
Section: -mentioning
confidence: 87%
“…The polyoxometalate silicotungstic acid has found utility in this regard as a sustainable hydrogenation agent for a number of organic transformations. In 2018, MacDonald et al [87] used the two-electron reduced form of this compound (H 6 SiW 12 O 40 , which they generated electrochemically with concomitant oxidation of water) as a source of protons and electrons for the reduction of a range of nitroarene compounds to their aniline analogues in (on the whole) good to excellent yields (Figure 17a). The silicotungstic acid could then be recycled, rereduced, and reused without any appreciable drop in catalytic performance.…”
Section: Decoupled Electrolysis For Chemical Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…By leveraging the electrochromic properties of Well-Dawson-type polyoxometalates based on K 10 231 The electrochromic properties are available in K 6 P 2 W 18 O 62 when it is combined with TiO 2 nanowires, resulting in excellent switching and transmittance properties. 232 Polyoxotungstates have been employed in a number of energy conversion and storage applications 36,43,228,[233][234][235][236][237][238][239][240][241][242] and sensors. 145,[243][244][245][246][247] 6 | POLYOXOMOLYBDATE Molybdenum trioxide with the formula MoO 3 has been applied as catalysts and synthesizing agent, and its polyoxometalate counterpart polyoxomolybdate has been widely studied to modulate their electronic and optoelectronic properties for energy conversion and storage applications.…”
Section: Polyoxotungstatementioning
confidence: 99%
“…4 However, instead of discharging this reduced redox mediator to make hydrogen, the authors instead used it to drive the chemical reduction of nitroarenes to their aniline derivatives. 5 Good to excellent yields of the anilines were reported, without the need to handle hydrogen gas or to employ any co-catalysts. The redox mediator could then be recycled and used again.…”
Section: Beyond Electrolysis: Decoupling Strategies In Fuel Cells Andmentioning
confidence: 99%